Detection of eae, bfpA, espA Genes on Diarrhoeagenic Strains of Escherichia coli Isolates - Agnes Sri Harti; Susi Iravati; Widya Asmara (Universitas Gadjah Mada, 2006)
The Enteropathogenic Escherichia coli (EPEC) is one of pathogenic strain of diarrheagenic E. coli group in children and infant that occurs in developing countries. The significant virulence factors in pathogenic EPEC are eaeA (E. coli attaching- effacing ), bfpA (bundle-forming pilus A) and espA (encoding secreted protein A) genes. The use of DNA probes to detect the virulence genes in E. coli in Indonesia is not common yet. In this experiment the gene fragments of eae, bfpA, and espA were used as probes to detect the EPEC among E. coli isolates from stool specimensin of diarrheic children attending Public Health Centers in Yogyakarta. The DNA samples were isolated from 49 diarrheagenic E. coli isolates. The DNA probes of eae, bfpA and espA were obtained by amplification of DNA fragment of EPEC O126 using PCR technique. Furthermore, those probes were used to identify the presence of those genes among E. coli isolates using hybridization technique. The results showed that 42 (85.7%) isolates were espA+, 25 isolates (51%) were eaeA+ (EPEC strains). Therefore among 25 isolates of EPEC, 20 isolates (80 %) among EPEC were bfpA+ (typical EPEC strains).